2018
DOI: 10.1680/jenge.15.00070
|View full text |Cite
|
Sign up to set email alerts
|

Biological aspects of microbial-induced calcite precipitation

Abstract: Microbially-induced calcite precipitation (MICP) is an emerging ground-modification technique. This paper presents the results of laboratory experiments that elucidate some biological factors affecting bioaugmentation and biostimulation strategies of MICP. Co-culture experiments suggest that ureolytic bacterium Sporosarcina pasteurii (DSMZ 33) might release the enzyme urease once introduced into a medium containing non-ureolytic bacterium Bacillus subtilis (DSMZ 6397) due to lysis by the latter, resulting in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…However, adding new bacteria can cause several problems, i.e., survivability of exogenous bacteria, uneven distribution, longer time needed for the permeation of bacteria, costly for the cultivation and special cautions required while mixing (DeJong et al 2010;Tsesarsky et al 2016). In the case of biostimulation, indigenous bacteria are stimulated to achieve calcium carbonate precipitation.…”
Section: Micp Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, adding new bacteria can cause several problems, i.e., survivability of exogenous bacteria, uneven distribution, longer time needed for the permeation of bacteria, costly for the cultivation and special cautions required while mixing (DeJong et al 2010;Tsesarsky et al 2016). In the case of biostimulation, indigenous bacteria are stimulated to achieve calcium carbonate precipitation.…”
Section: Micp Protocolsmentioning
confidence: 99%
“…Bioaugmentation is a process where urease-producing bacteria are added (injected) to the soil, whereas biostimulation takes advantage of the indigenous bacteria already present in the soil and stimulates them to precipitate calcite. Past studies (Burbank et al 2011;Burbank et al 2012;Gomez et al 2018;Tsesarsky et al 2016) showed that biostimulation is a superior alternative as the bacteria are already accustomed to the soil environment compared to augmented bacteria. Hence, this research investigates the applicability of biostimulation to clayey soils in minimizing their swelling potential and improving the strength.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the MICP treatment using a longer curing time [205,218], more number of treatments [37,40,74,94,163,170,175,263], higher CS concentration [40,175,205,223,231], greater bacterial density [205], or larger amount of injected bacteria [201] generally leads to a greater reduction in the permeability of the biocemented soil as more calcium carbonate would be precipitated with these conditions. On the other hand, Cheng et al [85,195] found that, for the same amount of calcium carbonate, UA of bacteria has a minor impact on the permeability of biocemented soil [85], while a lower saturation condition could maintain a relatively high residual permeability [195].…”
Section: Seepage Control Of Soilmentioning
confidence: 99%
“…Some other microorganisms, such as Myxococcus xanthus [27], Thraustochytrium striatum [28], Escherichia coli HB101 [29], Bacillus sphaericus [30], and Sarcina ureae [31], also have been applied for the MICP treatment. The UPB also can be enriched or isolated from the local soil [25,[32][33][34][35][36][37][38][39][40][41][42][43], groundwater [44] or waste-activated sludge [45,46], or in situ stimulated the natural indigenous bacteria [47][48][49][50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…The latter is the most encountered method in practice for soil stabilization. However, it was shown that biostimulation is a better alternative in a context of global warming as the reactivation of in situ microorganisms can be more vulnerable to the competitively with new bacteria [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%